Modeling and simulation of digital frequency relay for generator protection - Aman, M.M.; Jasmon, G.; Mokhlis, Hazlie; Khan, Q.A.; Bakar, A.H.A.; Karimi, M. (2012)
Modeling tools are useful for educational and industrial use. Such tools help the new engineers to simulate the power system under normal and faulted conditions. This paper presents the design and various data conversion steps of a digital frequency relay. The designed relay will cover both over and under frequency conditions. The digital relay has superiority over electromechanical relay in terms of accuracy and speed. The large frequency variations could lead to complete power system blackout. History has seen several blackouts due to frequency instability, either due to supply-demand unbalance or N-1 contingency. After distributed generation and the possible islanding issues, frequency relay has again gain the attention of the researchers and industrialists. The performance of proposed digital frequency relay will be observed under different system dynamics on MATLAB/SIMULINKÂ®.